Adaptive Sliding Mode Control of Lateral Stability of Four Wheel Hub Electric Vehicles - Li, Shou-Tao; Liu, Hui; Zhao, Di; Li, Qiu-Yuan; Tian, Yan-Tao; Wang, De-Jun; Yu, Ding-Li (International journal of automotive technology, 2020)
Some physical parameters of a hub motor-driven four-wheel electric vehicle will change when the vehicle turns or maneuvers and the parameter change is caused by the change of the driving conditions. An adaptive sliding mode control is proposed in this paper to maintain the vehicle’s stability by compensating for the change of these parameters. The control parameter being adapted is the converging rate of the system state towards the sliding mode. As the Lyapunov method is used, so both the vehicle stability and adaptive rate convergence are guaranteed. Moreover, the hierarchical control structure is adopted for this vehicle stability control system. The above adaptive sliding model control forms the upper-layer; while the lower-layer control is to distribute the upper torque to the four wheels in an optimal way, subject to several constraints. In addition, the best feasible reference of the yaw rate and the vehicle side slip angle are obtained and used in the control system. The developed method is simulated under the CarSim/MATLAB co-simulation environment to evaluate the system performance. The simulation results are compared with the non-adaptive existing sliding mode control, and show that the proposed method is superior under different conditions.